Defining educational objectives while using the method of case studies - Shapran, Ludmila (My University, 2015)
The article is devoted to the definition of educational objectives in line with the main tasks of business education, setting goals of specific cases (educational, pedagogical and developmental), functionality of the case study method and tasks to be solved in the process of its implementation are studied.
Keywords: economics and management education; didactic objectives; case-study method; educational objectives; дидактичні завдання; педагогічна ціль; економічний та управлінський напрями підготовки; кейс-метод; дидактические задания; педагогическая цель; кафедра ділової іноземної мови та міжнародної комунікації